Epidemiology and effects of fluid bolus administration in the paediatric emergency department. (23rd December 2019) - Solan, Tom; Stephens, David J; Williams, Amanda; Babl, Franz E; Long, Elliot
Abstract: Objective: Fluid bolus therapy (FBT) is recommended as the initial form of acute circulatory support for many disease processes. The epidemiology of its use in the ED is unknown. The aim of this study was to assess indications, use patterns and short‐term effects of FBT in a paediatric ED. Methods: Retrospective observational study in the ED of the Royal Children's Hospital, Melbourne, Australia (annual census >90 000) using hospital electronic medical record data for all patients who received an i.v. fluid bolus in the ED over the calendar year 2018 were included in the study. We extracted demographics, indications, volume, content of FBT as well as subsequent vital sign and biochemical changes. Results: One thousand five hundred and thirty‐nine fluid boluses were administered to 1343/90 000 children (1.5%), 1185 received 1, 123 received 2, 32 received 3, and 3 received 4 boluses. Fluid bolus volume of 10 mL/kg was used in 45.3%, 20 mL/kg in 35.7%, 500 mL in 6.4% and 1000 mL in 7.1%. The fluid content was 0.9% saline in 99.9% of cases. The most common indications for FBT were: vomiting/diarrhoea (23%), acute febrile illness (11%) and pneumonia or sepsis (10% each). FBT was associated with a reduction in median heart rate by 6 beats per minute ( P  < 0.01), reduction in mean blood pressure by 3 mmHg ( P  < 0.01), and reduction in venous lactate by 0.2 mmol/L ( P  < 0.01). Conclusions: Fluid bolus therapy is a commonly used intervention in the paediatric ED, most often for dehydration. Variability in indications, dose and effects of FBT warrant further exploration.